Sistem Informasi Kospala Di SMA Negeri 12 Bulukumba Dengan Notifikasi Whatsapp Gateway Berbasis Website - Naila Aulia; Husni Sulaiman; Imriani Idrus (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
KOSPALA Information System at SMA Negeri 12 Bulukumba with Website-Based WhatsApp Gateway Notifications. Thesis, Department of Information Systems, Bina Adinata Institute of Technology and Business (Supervised by: Husni Sulaiman S.Kom., M.Kom and Imriani Idrus, S.Si, M.M). This study aims to: (1) Design a KOSPALA Information System at SMA Negeri 12 Bulukumba with website-based WhatsApp Gateway Notifications to improve the effectiveness of extracurricular activity management; (2) Determine user responses to the developed system. The previous activity management system was still carried out manually through recording agenda books and physical correspondence, resulting in less effective management of member data, activity schedules, and parental permissions, frequent delays in information, and non-centralized data documentation. The system development method used is ADDIE which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The system was designed using Unified Modeling Language (UML), which includes use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The system was built using the PHP programming language with a MySQL database and is equipped with an automatic notification feature via WhatsApp Gateway. The results of the study indicate that: (1) the system was successfully designed and implemented, integrating member data, activity schedules, and parental permissions. All features, such as online registration, digital attendance, and activity notifications, functioned well. (2) User response to the system was very positive with a score of 85.3%, indicating that the system was well-accepted and used.